Influence of Work Supervision System, Communication and Emotional Intelligence on Employee Performance Development Planning Agency at Sub-National Level Labuhanbatu Regency - Zati Rizky Agung; Siti Lam’ah Nasution; Abd. Halim (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze the effect of work supervision, communication and emotional intelligence systems on employee performance at the Regional Development Planning Agency of Labuhanbatu Regency. The population in this study were 60 people. The sampling technique used was saturated sampling, so the sample size in this study was 60 people. The data collection method used a questionnaire/questionnaire. The results of multiple linear regression analysis obtained the equation Y = 1.063 + 0.803X1 + 0.564X2 + 0.166X3. In the partial test (t test) the regression coefficient of the work supervision system variable (X1) obtained a t value of 5.707 > t table 2.003 which means that the work supervision system variable has a positive and significant effect on the employee performance variable with a significant value of 0.000 < 0.05. The communication variable (X2) has a t-count value of 4.187 > t-table 2.003, which means that the communication variable has a positive and significant effect on the employee performance variable with a significant value of 0.000 <0.05. Emotional intelligence variable (X3) obtained t value of 2.105 > t table 2.003 which means that emotional intelligence variable has a positive and significant effect on employee performance variables with a significant value of 0.040 <0.05. The results of the F test obtained that the Fcount value of 56.845 > Ftable 2.77 with a significant value of 0.000 <0.05 which means that the work supervision system, communication and emotional intelligence simultaneously have a positive and significant effect on employee performance. The results of the coefficient of determination test indicate that the work supervision, communication and emotional intelligence system variables have an influence of 75.3% on the employee performance variable, while the remaining 24.7% is influenced by other variables outside this study.